Petroleum geological conditions and exploration potential of Lower Paleozoic carbonate rocks in Gucheng Area, Tarim Basin, China - Yinghui CAO; Shan WANG; Yajin ZHANG; Min YANG; Lei YAN; Yimin ZHAO; Junlong ZHANG; Xiandong WANG; Xiaoxiao ZHOU; Hongjiang WANG (Petroleum Exploration and Development, 2019)
Lower Paleozoic carbonate rocks are an important exploration area in craton area of the Tarim Basin, with the proven oil and gas reserves of more than 2.2×108 t, but no large-scale discovery has been made in the Gucheng area so far. The key issues restricting exploration are that the source rock, reservoir scale and law of oil and gas enrichment are unclear. By systematically examining the petroleum geological conditions of Lower Paleozoic carbonate rocks, the following findings are reached: (1) Source rocks of slope-basin facies developed in Cambrian-Lower Ordovician in the Gucheng area. (2) The dolomitized beach in the lower part of Ordovician Yingshan Formation has large-scale reservoirs, good reservoir-cap assemblage and developed gas source faults, and is an important field for increasing reserves and production in the near future; hydrocarbon enrichment is controlled by reservoir and gas source faults, and the central dolomitized beach zone is the main exploration area. (3) The Cambrian platform margin reef beach, large in scale, good in physical properties and close to source rocks, has the possibility to form monolithic gas field; the caprock and preservation conditions are the key factors for hydrocarbon enrichment; the northern part of the phases I and II platform margin reefs has better sealing conditions, and is the main direction of next exploration. (4) Limestone fault solution reservoirs in the upper part of Ordovician Yingshan Formation, controlled by faults and small in scale, but good in reservoir-cap combination, worth exploring. (5) The granular limestone beach of Ordovician Yijianfang Formation is well developed and gas-bearing, but short in exposure dissolution time, and the reservoirs are strongly heterogeneous, and are a potential exploration field. Key words: Tarim Basin, Gucheng Area, Lower Paleozoic, carbonate rock, petroleum geological conditions, exploration potential